2020
DOI: 10.3389/fmicb.2020.570926
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Against Phytopathogens and Inhibitory Activity on Solanine in Potatoes of the Endophytic Bacteria Isolated From Potato Tubers

Abstract: As an important global crop, the potato ( Solanum tuberosum L.) contains the endotoxin solanine that leads to human poisoning and major economic losses. Poisoning symptoms and even acute poisoning may occur when the content of solanine in potatoes exceeds 200 mg/kg. In addition, potatoes are susceptible to some pathogenic bacteria, including Streptomyces scabies and Erwinia carotovora subsp. atroseptica (Van Hall) dye, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 60 publications
(62 reference statements)
1
28
0
1
Order By: Relevance
“…In other words, the rarefaction curves showed that the sequencing work was relatively comprehensive in covering the bacterial diversity, as the curves tended to approach saturation, indicating that the selected sequence data adequately reflected the bacterial abundance of these samples. The alpha-diversity analyses, including Shannon, Sobs, Simpson, Chao, Ace, and Coverage, were used to detect the distribution of endophytic microbial composition on OTU level and estimated the endophytic community complexity ( Liu J. M. et al, 2020 ; Supplementary Table 2 ). The lower Simpson index value but higher Shannon index of group J10_15cm indicated greater community diversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the rarefaction curves showed that the sequencing work was relatively comprehensive in covering the bacterial diversity, as the curves tended to approach saturation, indicating that the selected sequence data adequately reflected the bacterial abundance of these samples. The alpha-diversity analyses, including Shannon, Sobs, Simpson, Chao, Ace, and Coverage, were used to detect the distribution of endophytic microbial composition on OTU level and estimated the endophytic community complexity ( Liu J. M. et al, 2020 ; Supplementary Table 2 ). The lower Simpson index value but higher Shannon index of group J10_15cm indicated greater community diversity.…”
Section: Resultsmentioning
confidence: 99%
“…The raw reads were stored in the Sequence Read Archive of the National Center for Biotechnology Information (NCBI) database. Sequencing data were processed and analyzed according to the method in Liu J. M. et al (2020) ( Supplementary Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIPC ([isopropyl-N-(3-chlorophenyl) carbamate) is particularly important as a sprout suppressant for potatoes during storage. However, CIPC has been proven not to be safe for humans and the environment in recent years [101]. Therefore, alternate sprout suppressant approaches, for example constant ethylene supplement, could be used to suppress post-harvest sprouting [102].…”
Section: Postharvestmentioning
confidence: 99%
“…It was reported that endophytic bacteria colonized through plant tissue into vegetative and reproductive organs of plants. Plants with prior inoculation with endophytes reduce the diseases of fungal, viral, and bacteria and prevent insects and nematodes attack [52][53][54].…”
Section: Secondary Metabolites and Biocontrol Agentsmentioning
confidence: 99%